2008
DOI: 10.1007/s10546-008-9317-7
|View full text |Cite
|
Sign up to set email alerts
|

Footprints in Homogeneously and Heterogeneously Driven Boundary Layers Derived from a Lagrangian Stochastic Particle Model Embedded into Large-Eddy Simulation

Abstract: A Lagrangian stochastic (LS) model, which is embedded into a parallelised largeeddy simulation (LES) model, is used for dispersion and footprint evaluations. For the first time an online coupling between LES and LS models is applied. The new model reproduces concentration patterns, which were obtained in prior studies, provided that subgrid-scale turbulence is included in the LS model. Comparisons with prior studies show that the model evaluates footprints successfully. Streamwise dispersion leads to footprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 60 publications
4
70
0
Order By: Relevance
“…Even though the blending-height analysis clearly suggested that the VLAS measurements cannot be considered to yield representative estimates of the area-averaged surface sensible heat flux, it would be necessary to perform a more sophisticated footprint analysis for the LES to confirm that the VLAS "sees" only the surface fluxes in its footprint area. In a future study we will employ a Lagrangian footprint model, embedded into the LES (see Steinfeld et al 2008), over the heterogeneous LITFASS-2003 terrain in order to determine more elaborate footprints that take into account the surface heterogeneity. T from the spectral method to the respective value derived from the dissipation method, and b C 2 T from both the spectral and the corrected dissipation method.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the blending-height analysis clearly suggested that the VLAS measurements cannot be considered to yield representative estimates of the area-averaged surface sensible heat flux, it would be necessary to perform a more sophisticated footprint analysis for the LES to confirm that the VLAS "sees" only the surface fluxes in its footprint area. In a future study we will employ a Lagrangian footprint model, embedded into the LES (see Steinfeld et al 2008), over the heterogeneous LITFASS-2003 terrain in order to determine more elaborate footprints that take into account the surface heterogeneity. T from the spectral method to the respective value derived from the dissipation method, and b C 2 T from both the spectral and the corrected dissipation method.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of PALM have been provided by Raasch and Etling (1998) and Raasch and Schr枚ter (2001). PALM has been successfully applied for investigations of the neutrally (Letzel et al 2008) and weakly stably stratified boundary layer (Beare et al 2007;Steinfeld et al 2007) as well as the homogeneously heated (Schr枚ter et al 2000;Raasch and Franke 2011) and heterogeneously heated CBL (Raasch and Harbusch 2001;Letzel and Raasch 2003;Inagaki et al 2006;Steinfeld et al 2008;Maronga and Raasch 2013) and is therefore well suited for this study.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Markkanen et al: Lagrangian footprint model comparison in 2-D Lagrangian particles (Cai and Leclerc, 2007) or the particles are released during LES run in which case the particles experience the flow field development in real time (Steinfeld et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…of Helsinki (Rannik et al, 2000;Markkanen et al, 2003;Rannik et al, 2003) for forward simulations (FW). As a reference we use the LES model PALM (Raasch and Etling, 1998;Raasch and Schr枚ter, 2001) which simulates trajectories of a large number of particles simultaneously with general flow field calculations (Steinfeld et al, 2008). From this data the footprints are determined in a manner similar to that used in conventional forward LS models (Kurbanmuradov et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation